Detection and identification of dyes in blue writing inks by LC-DAD-orbitrap MS. (April 2016) - Sun, Qiran; Luo, Yiwen; Yang, Xu; Xiang, Ping; Shen, Min
Highlights: Screening analysis of acid and basic dyes in blue writing inks. Method validation. Thirty blue ink samples were analyzed and nine reference dyes were detected. Four unknown dyes detected in ink samples were identified using Orbitrap MS. Abstract: In the field of forensic questioned document examination, to identify dyes detected in inks not only provides a solid foundation for ink discrimination in forged contents identification, but also facilitates the investigation of ink origin or the study regarding ink dating. To detect and identify potential acid and basic dyes in blue writing inks, a liquid chromatography-diode array detection-Orbitrap mass spectrometry (LC-DAD-Orbitrap MS) method was established. Three sulfonic acid dyes (Acid blue 1, Acid blue 9 and Acid red 52) and six triphenylmethane basic dyes (Ethyl violet, Crystal violet, Methyl violet 2B, Basic blue 7, Victoria blue B and Victoria blue R) were employed as reference dyes for method development. Determination of the nine dyes was validated to evaluate the instrument performance, and it turned out to be sensitive and stable enough for quantification. The method was then applied in the screening analysis of ten blue roller ball pen inks and twenty blue ballpoint pen inks. As a result, including TPR (a de-methylated product of Crystal violet), ten known dyes and four unknown dyes were detected in the inks. The latter were further identified as a de-methylated product of Victoria blue B, Acid blue 104, Acid violet 49 and Acid blue 90, through analyzing their characteristic precursor and product ions acquired by Orbitrap MS with good mass accuracy. The results showed that the established method is capable of detecting and identifying potential dyes in blue writing inks.